Numerical Simulation of Copper Deposition in the Hull Cell Based on Butler-Volmer Kinetics. Issue 12 (31st August 2020) - Kovácsovics, I.; Patzelt, T.; Pilz, U.; Herrmann, J.; Bund, A.
Abstract : In industry plating baths are often characterized by visual evaluation of a Hull cell deposition. In an academic approach, kinetic parameters are determined with cyclic voltammetry to obtain a deeper understanding of reaction mechanisms. In this paper we combine both approaches and show how via numerical simulations based on the boundary element method kinetic parameters can be extracted from Hull cell experiments. This combined method enables a better understanding of industrial electroplating processes without losing important information about coating and visual appearance. The validation is done in an acidic copper system using the kinetic parameters obtained from cyclic voltammetry for simulating the current density distribution and the cell voltage of a Hull cell deposition, followed by a comparison with experimental data. As an additional insight obtained from this study, the presence of O2 lowers the anodic transfer coefficient, while Cl – ions in the electrolyte increase the exchange current density.